Synthesis, structure-activity relationship and molecular docking studies of 3-O-flavonol glycosides as cholinesterase inhibitors. Issue 12 (23rd July 2018) - Mughal, Ehsan Ullah; Javid, Asif; Sadiq, Amina; Murtaza, Shahzad; Zafar, Muhammad Naveed; Khan, Bilal Ahmad; Sumra, Sajjad Hussain; Tahir, Muhammad Nawaz; Kanwal,; Khan, Khalid Mohammed
Graphical abstract: Abstract: The prime objective of this research work is to prepare readily soluble synthetic analogues of naturally occurring 3- O -flavonol glycosides and then investigate the influence of various substituents on biological properties of synthetic compounds. In this context, a series of varyingly substituted 3- O -flavonol glycosides have been designed, synthesized and characterized efficiently. The structures of synthetic molecules were unambiguously corroborated by IR, 1 H, 13 C NMR and ESI-MS spectroscopic techniques. The structure of compound22 was also analyzed by X-ray diffraction analysis. All the synthetic compounds (21 –30 ) were evaluated for in vitro inhibitory potential against cholinesterase enzymes. The results displayed that most of the derivatives were potent inhibitors of acetylcholinesterase (AChE) and butyrylcholinesterase (BChE) with varying degree of IC50 values. The experimental results were further encouraged by molecular docking studies in order to explore their binding behavior with the active pocket of AChE and BChE enzymes. The experimental and theoretical results are in parallel with one another.